Transformasi Spiritual Dalam Ucap-Ucap Rangda Pementasan Napak Pertiwi Pura Dalem Penataran Banjar Taman Sari Sanur - Ida Ayu Intan Agustiari Manuaba; I Made Dian Saputra; I Putu Suweka Oka Sugiharta (Jayapangus Press, 2026)
Sesolahan Napak Pertiwi at Pura Dalem Penataran is a sacred artistic practice that combines religious expression, the aesthetics of Barong-Rangda dance drama, and the preservation of the Balinese language. One important element in this performance is ucap-ucap Rangda, which functions not only as a dramatic element, but also as a sacred expression containing literary, symbolic, and spiritual values. This study aims to describe the formation process of ucap-ucap Rangda, the meanings and signs contained within it, and the spiritual conditions that emerge during the implementation of Sesolahan Napak Pertiwi. This research applies a qualitative approach supported by structuralism theory and spiritual transformation theory. Data were collected through observation, interviews, documentation, and literature study, then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results show that ucap-ucap Rangda was formed through a process of traditional inheritance related to the history of the performance and the repeated use of sacred lyrics in a ritual context. Ucap-ucap Rangda contains distinctive linguistic structures, symbols of religious power, and spiritual signs that connect the performance with the beliefs of its supporting community. Furthermore, the spiritual conditions in Sesolahan Napak Pertiwi appear in four stages: initial awareness, purification, transcendental experience, and realignment. These stages indicate an inner transformation from self-preparation toward sacred unity and finally a return to socio-religious balance. This study concludes that Sesolahan Napak Pertiwi serves not only as a sacred performance, but also as a medium for preserving the Balinese language, transmitting spiritual values, and strengthening local cultural identity.